Pengaruh Efektivitas Sistem Informasi Akuntansi (SIA), Teknik Pengguna SIA, dan Pengendalian Internal Terhadap Kinerja Individu (Studi Kasus di PT. Mardika Griya Prasta) - I G. N. Oka Ariwangsa; Dewa Ayu Rina Dewi Paramitha (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
The following research aims to determine the effect of effectiveness AIS, AIS user techniques, and internal control partially and simultaneously on individual performance, with a sample by 40 people. The research instrument is a questionnaire from the Validity Test and Reliability Test. Data analysis techniques with the help of SPSS ver.26. The final results show that partially the effectiveness of AIS, AIS user techniques, and internal control have a significant positive effect on individual performance and simultaneously the effectiveness of AIS, AIS user techniques and internal controls have a significant effect on individual performance. The influence of the independent variable on the dependent variable is 73.4%. Advice that can be given is to improve individual performance at PT. Mardika Griya Prasta matches to update the information system used, so that later it will be able to support individual/employee performance. Besides that PT. Mardika Griya Prasta is expected to always implement internal control properly.